Laparoscopic total oncologic gastrectomy - Valsangiacomo, Pablo; Campos, Maite; Perdomo, Mauro; Bentancur, Martín; González González, Daniel (Cirugía del Uruguay, 2020)
Introduction Laparoscopic oncological gastrectomy has increased in recent years due to postoperative benefits, maintaining oncological principles. We describe the main technical aspects of laparoscopic total oncological gastrectomy. Description of contents Patient with advanced subcardial gastric adenocarcinoma. We started with peritoneal lavage, opening of the greater omentum, resecting the nodes of group 4 and 5, section of the right gastroepiploic pedicle, resecting group 6. Section of the duodenum and lymphadenectomy of group 8, 9 and 11. Stomachic coronary artery section (group 7). Resection of the lesser omentum to the esophageal hiatus and resection of ganglion groups 1, 2 and 3. We section the esophagus, extract the piece and resect the greater omentum. Reconstruction of the Roux-en-Y digestive transit. Conclusions Laparoscopic oncological gastrectomy is a feasible and safe technique. Its performance requires experience in esophagogastric cancer surgery and advanced laparoscopic surgery.